2023
DOI: 10.1001/jamapediatrics.2023.0333
|View full text |Cite
|
Sign up to set email alerts
|

Birth-Based vs Fetuses-at-Risk Approaches for Assessing Neonatal Mortality Rate by Race

Abstract: This cohort study assesses 5-year race-stratified neonatal mortality and prevalence of preterm births in the US using birth-based and fetuses-at-risk approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Although the fetus at risk approach and its modification is not universally accepted, 28 it focuses attention on the notion that burden to the clinician, as well as the family, is dependent upon both rate and volume. 29 Similar findings were reported by Wu et al who state that this paradox (the Black disadvantage estimated by the fetus at risk approach) seen when GA specific neonatal mortality rate is stratified by risk factors such as race, “may be explained if more neonates without congenital anomalies are born at earlier GA among Black vs White mothers.” 30 Our study of very preterm infants is limited to California, which may have population and healthcare-specific differences from other states. For example, our 2020 infant mortality of 3.92 is one of the lowest in the country.…”
Section: Discussionmentioning
confidence: 99%
“…Although the fetus at risk approach and its modification is not universally accepted, 28 it focuses attention on the notion that burden to the clinician, as well as the family, is dependent upon both rate and volume. 29 Similar findings were reported by Wu et al who state that this paradox (the Black disadvantage estimated by the fetus at risk approach) seen when GA specific neonatal mortality rate is stratified by risk factors such as race, “may be explained if more neonates without congenital anomalies are born at earlier GA among Black vs White mothers.” 30 Our study of very preterm infants is limited to California, which may have population and healthcare-specific differences from other states. For example, our 2020 infant mortality of 3.92 is one of the lowest in the country.…”
Section: Discussionmentioning
confidence: 99%
“…Preterm birth (PTB; live-birth <37 weeks gestation) is the leading cause of death in children under age 5 years [1]. Among US singletons born without congenital anomalies, PTB prevalence increased from 7.6% to 8.1% [2] between 2014 and 2018, with Black women having the highest (11.2%) and White women having the lowest prevalence (7.2%) [2]. Pacific Islander women in the United States (PTB prevalence: 11.2%) [3] also have a higher risk of PTB compared with White women [3], but our understanding of risk factors underlying this disparity is limited because Pacific Islander individuals have been traditionally aggregated with Asian American individuals, whose demographic characteristics and biomedical risk profiles are quite dissimilar [4].…”
Section: Introductionmentioning
confidence: 99%
“…There are several ways to address the induced selection bias. By applying the fetuses-at-risk approach, we recently demonstrated that neonatal mortality rate (<28 days) was roughly 3 times higher among Black neonates than White neonates born extremely preterm, which contrasted standard stratified (ie, biased) analysis where the neonatal mortality rate was slightly lower among Black neonates compared with White neonates born extremely preterm . In the setting of infant mortality, inverse-probability weighting may be an applicable approach to address collider stratification bias.…”
mentioning
confidence: 99%